Hubungan Keteraturan Ibu Hamil Dalam Melaksanakan Kunjungan Antenatal Care (ANC) Terhadap Hasil Deteksi Dini Risiko Tinggi Ibu Hamil di Poli KIA RSUD Gambiran Kota Kediri - Sumy Dwi Antono; Dwi Estuning Rahayu (coba, 2014)
Each pregnancy can develop normally, but it is difficult to know before that the pregnancy would be a problem, Antenatal care is an important way to monitor and support the normal maternal health and to detect any abnormalities in normal pregnancy. This study aims to determine the correlation of Pregnant mother’s Regularity in visiting Antenatal Care (ANC) on the Results from Early Detection of High Risk Pregnancy in Poli KIA RSUD Gambiran Kediri. This research is analytic correlation using a case-control study design. The populations in this study were all third trimester pregnant mother with high risk in Poli KIA RSUD Gambiran Kediri. The number of samples is 28 people who were taken with simple random sampling technique. Measuring instruments used KIA books and Antenatal care documentation. The results will be analyzed using Chi Square test with one sample with a standard error 5% (0,05). Based on the analysis results obtained values = 14,28 > 3,841 so it can be stated that there is the correlation of Pregnant mother’s Regularity in visiting Antenatal Care (ANC) on the Results from Early Detection of High Risk Pregnancy in Poli KIA RSUD Gambiran Kediri. The results are mostly high-risk pregnant mother are irregular in implementing Antenatal care. The recommendations of this research is needed to conduct counseling from a health counselor to all pregnant mother about the importance of prenatal care regularly to add the knowledge about pregnancy and also to allows health workers to detect early if there is a complication of pregnancy and as an effort to increase utilization of health services for mother pregnant. Key words : regularity of ANC, Antenatal Care (ANC), Early Detection of High Risk